Bolivia : Statistical Annex. (IMF Staff Country Reports; Country Report, 2000)
In this paper, the statistical data of macroeconomic flows, national accounts, production, and employment, combined public sector, financial sector, and external sector are presented in detail. They are listed as follows: aggregate supply and demand, the volume of mining production, mining reserves and production, consumer prices, private sector wages, operations of the central government and central administration, monetary survey, selected index rates, open market bills, summary accounts of the financial system, exports by principal products, imports by economic category, direction of trade, and so on.